PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN GETARAN DAN GELOMBANG DI SMP NEGERI 1 KOTA TERNATE - Lisna Lisna; Ridwan Jusuf; Masrifah Masrifah (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
This study aims to determine increases Student Results Using problem-based learning model on the subject of vibrations and waves in class VIIIJ SMP Negeri 1 Ternate. The subjects were students of class VIIIJ the number of 27 students consisting of 16 male students and 11 female students. While the observer is composed of two teachers of subjects. This type of research is research grade tindaka using two cycles through four stages: planning, action, observation, and reflection. Data collection techniques used were observation and tests. The instrument used in this study is the observation and question. Analysis of the data used is quantitative descriptive approach. The results showed the average percentage of learning outcomes increased from 40.75% in the first cycle to 77.78% in the second cycle. The mean for the activities of teachers in the first cycle with the average of 61.67% and are included in the category fairly and on the second cycle increased to 77%, including both categories. Activity of students in the first cycle of 47.91% is included in the poor category and the second cycle increased by 71% is included in both categories. Conclusions from this research is the application of problem-based learning model can improve student learning outcomes VIIIJ grade SMP Negeri 1 of Ternate in the academic year 2011/2012. Keywords: Model of problem-based learning, student learning outcomes.